2019
DOI: 10.1111/jebm.12361
|View full text |Cite
|
Sign up to set email alerts
|

Critical evaluation of arguments opposing male circumcision: A systematic review

Abstract: Objective To systematically evaluate evidence against male circumcision (MC). Methods We searched PubMed, Google Scholar, EMBASE and Cochrane databases. Results Database searches retrieved 297 publications for inclusion. Bibliographies of these yielded 101 more. After evaluation we found: Claims that MC carries high risk were contradicted by low frequency of adverse events that were virtually all minor and easily treated with complete resolution. Claims that MC causes psychological harm were contradicted by st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 365 publications
(932 reference statements)
0
52
0
Order By: Relevance
“…Could it be that being duped by anti-circumcision propaganda leads to distress, and hence sexual disfunction? MC opponents make many false claims about the effect of circumcision on sexual function and pleasure which may lead to psychological distress in those deceived [40]. This makes misleading articles such as ES&J's particularly pernicious as they further a false narrative of circumcision causing harm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Could it be that being duped by anti-circumcision propaganda leads to distress, and hence sexual disfunction? MC opponents make many false claims about the effect of circumcision on sexual function and pleasure which may lead to psychological distress in those deceived [40]. This makes misleading articles such as ES&J's particularly pernicious as they further a false narrative of circumcision causing harm.…”
Section: Discussionmentioning
confidence: 99%
“…Given Earp's long history of writing anti-circumcision polemics, one can only suspect that the article critiqued here is just another attempt by circumcision opponents to build a body of literature that they can cite in support of their misguided agenda. They appear to feel the need to do this because most of the literature does not support their claims [40]. The need for journal editors and reviewers to be alert to the contents of manuscripts with a clear anti-circumcision agenda is becoming more important than ever, even more so considering MC's vital importance in HIV epidemic settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Risk-benefit analyses reported that benefits exceed risks by 100-200 to 1. To maximize benefits and minimize risks, the evidence supported early infant male circumcision rather than arguments that the procedure should be delayed until males are old enough to decide for themselves (Morris et al 2019).…”
Section: Critique Of the Practicementioning
confidence: 99%
“…Most claims have been based on anecdotes or low-quality surveys. An extensive systematic review has recently evaluated the claims by MC opponents and found them to be based on speculation or misinformation [11].…”
Section: Introductionmentioning
confidence: 99%